Wayang Edu: digital application for Wayang Kulit Kelantan - Fara Dayana Mohd Jufry; Nor Masharah Husain; Mohammad Naquiddin Tajul Ariffin (Institute of Advanced Engineering and Science, 2024)
Wayang Kulit Kelantan (WKK) is a traditional performance that has a long process in the learning session. This covers various aspects such as the background of the performance, repertoire, gambalan (puppets), as well as musical instruments and songs. This knowledge requires at least a year to understand the skills and techniques used. Therefore, Wayang Edu is a digital application built based on the analyze, design, development, implementation, evaluation (ADDIE) model to save learning time with traditional practitioners. The majority of users acknowledge that Wayang Edu offers a wealth of information and enables them to gain in-depth knowledge. Consequently, utilizing visual elements to convey messages is more impactful compared to traditional learning methods. Apart from that, Wayang Edu can be used anywhere at the user’s convenience. With the interaction found in the application, Wayang Edu has been used by students as a platform to get additional information about WKK.